Hollandia Haven â Hollandia Binnen: Two Historic Towns in Jayapura City - Baharuddin, Alfini (TAWARIKH, 2017)
ABSTRACT: The history of the city seems to be beneficial in urban studies. Thematically, the discussion of the city is not only to look the city from the structural aspects, but also look at the historical reconstruction. The most important aspect of historical reconstruction is the time-bound development. Therefore, the thematic discussion of the city is essential to incorporate the discussion structurally with regard to the chronological aspect. This study relates to Jayapura City in Papua Province, that is located at the eastern end of Indonesia and directly borders with neighboring countries, PNG (Papua New Guinea). The geographical conditions of Jayapura City are very diverse and dominated by hills that lead to the formation of separated urban areas. Currently, there are two major parts of the urban areas well-known as Jayapura and Abepura. Historically, Jayapura and Abepura were two old urban towns, namely âHollandia Havenâ and âHollandia Binnenâ. The existence of two parts of the urban areas in Jayapura City is one of the interesting things to be studied to determine its relevance to historical factors of Jayapura City. The division of developmental stages into some phases was carried out to understand how the pattern of historical development of Jayapura City is. Results of the study showed that the two urban towns have existed since the established of Jayapura City and survived to date. The presence of both old towns form the characteristics of ââtwo cities within a cityâ.KEY WORDS: Historic Towns; Two Cities; Hollandia Haven; Hollandia Binnen; Jayapura City.About the Author: Alfini Baharuddin is a Doctoral Student at the Department of Architecture and Planning, Faculty of Engineering UGM (Gadjah Mada University), Jalan Grafika, Yogyakarta; and a Lecturer at the Department of Architecture USTJ (Jayapura University of Science and Technology), Jalan Raya Sentani, Padang Bulan, Abepura, Jayapura, Papua, Indonesia. For academic interests, the author is able to be contacted via e-mail at: alfinibaharuddin@yahoo.comHow to cite this article? Baharuddin, Alfini. (2017). âHollandia Haven â Hollandia Binnen: Two Historic Towns in Jayapura Cityâ in TAWARIKH: International Journal for Historical Studies, Vol.8(2) April, pp.143-152. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (October 25, 2016); Revised (January 15, 2017); and Published (April 28, 2017).